Theoretical Description Of A Reparamatrization of Discrete Two Parameter Poisson Lindley Distribution for Modeling Waiting And Survival Times Data - Adhikari, Tanka Raj (Tribhuvan University Journal, 2016)
In this research paper, the theoretical description of are paramatrization of a discrete two-parameter Poisson Lindley Distribution, of which Sankaran’s (1970) one parameter Poisson Lindley Distribution is a special case, is derived by compounding a Poisson Distribution with two parameters Lindley Distribution for modeling waiting and survival times data of Shanker et al. (2012).The first four moments of this distribution have derived. Estimation of the parameters by using method of moments and maximum likely hood method has been discussed.